2009
DOI: 10.4319/lom.2009.7.81
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray and photoionization mass spectrometry for the characterization of organic matter in natural waters: a qualitative assessment

Abstract: Fourier‐transform ion cyclotron resonance mass spectrometry (MS) has demonstrated potential to revolutionize the fields of limnology and chemical oceanography by identifying the individual molecular components of organic matter in natural waters. The use of MS for this purpose is made possible by the electrospray technique which successfully ionizes polar, nonvolatile organic molecules. Another recently developed ion source, atmospheric pressure photoionization (APPI), extends MS capabilities to less polar mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(225 citation statements)
references
References 75 publications
8
216
1
Order By: Relevance
“…_ 1 ) T D $ F I G ] On the other hand, because in most cases the majority of peaks at even m/z are assigned to the 13 C isotope of peaks in high resolution mass spectra of NOM, only peaks at odd m/z were considered for CHO-molecular formulas assignment in the previous studies [5,19]. However, interestingly, during processing mass spectra in MALDI negative mode in our study, a significant portion of peaks at even m/z can also be assigned as CHOmolecules except for the 13 C isotope peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…_ 1 ) T D $ F I G ] On the other hand, because in most cases the majority of peaks at even m/z are assigned to the 13 C isotope of peaks in high resolution mass spectra of NOM, only peaks at odd m/z were considered for CHO-molecular formulas assignment in the previous studies [5,19]. However, interestingly, during processing mass spectra in MALDI negative mode in our study, a significant portion of peaks at even m/z can also be assigned as CHOmolecules except for the 13 C isotope peaks.…”
Section: Resultsmentioning
confidence: 99%
“…However, during ESI analysis, only some polar and moderately polar molecules of NOM can be ionized by ESI, and most of non-polar compounds cannot be detected [11]. Recently, some reports combined ESI and APPI ionization methods to characterize DOM and compared the obtained mass spectra [12,13]. The results suggested that APPI tended to ionize smaller and less polar molecules, whereas ESI produces ions that in general contain more oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements of analytical methods to identify whole classes of compounds such as amino acids, peptides, proteins and carbohydrate-like compounds are being made combining chromatography techniques with highly sensitive detectors that can approach the nanomolar range (Kaplan & Newbold, 2003). Characterization of DOC should also consider recent technics of mass spectrometry in organic molecules such as electrospray and atmospheric pressure photoionization (Hockaday et al, 2009), compounds could be determined by gas chromatography-mass spectrometer (Jaffé et al, 2012) and biodegradable DOC measured with bioreactors (McLaughlin & Kaplan, 2013).…”
Section: Perspectivesmentioning
confidence: 99%
“…From these diagrams, one can parse the formulae by regions of the van Krevelen diagram that denote molecular similarities with groups of compounds such as lipid, lignin, tannin, or condensed aromatics [42][43][44]. The whole and acid-soluble samples encompass all of these regions, giving van Krevelen diagrams that are very similar to one another (Figure 5a and b).…”
Section: Characterization From Fticr-ms Measurementsmentioning
confidence: 99%